Development of a Moisture-Modified Maturity Model for Portland Cement Concrete Pavements - Jin-Hoon Jeon; Seungwook Lim; Dan Zollinger (The Baltic Journal of Road and Bridge Engineering)
Different mathematical models have been developed to represent the relationship between strength and maturity of concrete. The linear relationship between double logarithmic strength and logarithmic maturity can be implemented in practice to monitor the in-place strength gain and time of opening under variable temperature conditions. Moisture of concrete was considered within the context of existing maturity concepts as a means for improving the predictability of concrete strength. A moisture modification factor developed by Bazant on the basis of Powers’ work was modified and included in an existing temperature-based maturity model. An improved relationship between relative strength and maturity was established by using the corrected moisture modification factor.